Endovascular Stent Graft Repair of Suture-Line Pseudoaneurysm Following Ascending Aorta Replacement. (April 2014) - Zicho, David; Cartwright, Neil; Bizzarri, Federico; Malkin, Christopher; Cross, Michael; Mcpherson, Simon; Kaul, Pankaj; Puppala, Sapna
Ascending aorta pseudoaneurysm (AAPA) is an uncommon complication following replacement of the ascending aorta with a prosthetic graft, carry a high risk of rupture, and warrant urgent intervention. The open surgical procedure "gold standard" of care is not always favorable, as the reoperations are technically more difficult or patient's general condition doesn't allow proceeding. Case discussed is an 80-year-old male patient who presented with worsening cough and hemoptysis. He underwent ascending aorta replacement 10 years ago. Computed tomography (CT) scan revealed a contrast-filled mediastinal mass communicating with the ascending aorta and extended into the right lung. Due to the patient's advanced age, friability and clinical condition, combined with the position of the AAPA behind the sternum, surgery was deemed to be high risk. However, favorable anatomical conditions provided a safe landing zone for an endovascular stent. The patient underwent closed procedure. Postprocedure CT showed complete obliteration of the AAPA.